2020
DOI: 10.1111/cts.12809
|View full text |Cite
|
Sign up to set email alerts
|

Febuxostat, But Not Allopurinol, Markedly Raises the Plasma Concentrations of the Breast Cancer Resistance Protein Substrate Rosuvastatin

Abstract: Xanthine oxidase inhibitors febuxostat and allopurinol are commonly used in the treatment of gout. Febuxostat inhibits the breast cancer resistance protein (BCRP) in vitro. Rosuvastatin is a BCRP substrate and genetic variability in BCRP markedly affects rosuvastatin pharmacokinetics. In this study, we investigated possible effects of febuxostat and allopurinol on rosuvastatin pharmacokinetics. In a randomized crossover study with 3 phases, 10 healthy volunteers ingested once daily placebo for 7 days, 300 mg a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…On the other hand, among the clinically-used inhibitors for the production of uric acid (i.e., allopurinol, febuxostat, and topiroxostat), only febuxostat, to the best of our knowledge, strongly and clinically inhibits ABCG2 function as a urate transporter [ 35 ]. This is also supported by a recent clinical study that showed orally-administered febuxostat inhibits intestinal ABCG2 in humans [ 46 ]. In this context, the efficacy of febuxostat as an SUA-lowering drug can be partially blocked by ABCG2 inhibition, except in cases of completely null ABCG2 function.…”
Section: Discussionsupporting
confidence: 62%
“…On the other hand, among the clinically-used inhibitors for the production of uric acid (i.e., allopurinol, febuxostat, and topiroxostat), only febuxostat, to the best of our knowledge, strongly and clinically inhibits ABCG2 function as a urate transporter [ 35 ]. This is also supported by a recent clinical study that showed orally-administered febuxostat inhibits intestinal ABCG2 in humans [ 46 ]. In this context, the efficacy of febuxostat as an SUA-lowering drug can be partially blocked by ABCG2 inhibition, except in cases of completely null ABCG2 function.…”
Section: Discussionsupporting
confidence: 62%
“…In the past, probenecid was used to sustain the serum concentration of penicillin, an OAT1/3 substrate 28 . Recently, it was reported that febuxostat increased the blood concentration of methotrexate and rosuvastatin, which are ABCG2 substrates 29 , 30 . In the present study, probenecid and benzbromarone should have functioned as OAT1/3 inhibitors and febuxostat as an ABCG2 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have been conducted to examine the FBX anti-cancer activity [ 16 , 42 , 43 ], with particular regard to its ability to enhance cancer cells death via apoptosis and decrease the chemotherapy resistance, then representing a promising candidate for cancer treatment. Additionally, based on its ability to reduce uric acid production in the body, this drug has been used for the treatment of tumor lysis syndrome, a metabolic impairment that arises in cancer patients [ 15 , 44 ].…”
Section: Discussionmentioning
confidence: 99%